Outcome of benign strictures in ulcerative colitis. (13th March 2011) - Ignjatovic, A; Tozer, P; Grant, K; Wilson, J; Hart, A L; Jenkins, J T; Thomas-Gibson, S; Clark, S K; Saunders, B P
Abstract : Introduction: Long standing ulcerative colitis (UC) is associated with an increased risk of colorectal cancer (CRC), with a cumulative incidence of about 15% at 30 years. The finding of a colonic stricture in a patient with colitis raises the possibility of neoplasia. Unlike in Crohn's disease, benign strictures in UC are rare and historically have been managed surgically with colectomy, partly due to difficulty of excluding cancer within the stricture. Radical surgery carries a risk of major morbidity including permanent stoma formation and segmental colectomy is currently not considered appropriate due to oncologic risk. The authors aimed to assess the outcome of the patients with benign strictures in UC who were managed non-operatively. Methods: Patients who had a colonoscopy between January 2003 and December 2008 at our institution and were found to have a stricture without proven malignancy within a segment of colitis were retrospectively identified from the endoscopic database. Those patients who had a follow-up of more than 24 months were included. Colonoscopy and histopathology reports and clinical notes were reviewed. Results: In the study period, 15 patients (6 female, median age 49 years) underwent colonoscopy for UC and were found to have a benign stricture. The median follow-up was 36 months. 14 of 18 strictures were left sided; mean duration of the stricture was 2.9 years (SD 2.1 years) and mean length of the stricture was 3.3 cm (SD 2.8 cm). Only two patients were symptomatic and both underwent endoscopic balloon dilatation. Two others underwent dilatation to allow passage of the colonoscope into the proximal colon. One patient ultimately developed CRC, but not within the strictured area of the colon. Two patients underwent surgery, one for CRC outside the stricture and one for what was revealed to be extrinsic compression secondary to endometriosis. One patient developed minor bleeding following endoscopic dilatation, which was managed conservatively. Conclusion: Although uncommon, benign strictures are a recognised complication of long standing UC. Careful and detailed consideration including histological and radiological assessment is needed to rule out dysplasia and malignancy. In this series, the majority of patients did not require intervention as the strictures were asymptomatic and ongoing endoscopic surveillance of the remainder of the colon was possible. Endoscopic balloon dilatation was safe and prevented the need for major surgery in four patients while allowing continued endoscopic surveillance. Reconsideration of the place of conservative management and segmental colectomy in benign UC strictures through larger studies may be appropriate.